PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS MACROMEDIA FLASH PADA PEMBELAJARAN TEMATIK TERPADU KELAS IV SEKOLAH DASAR - Fadhilla Imanda Azzahra; Yanti Fitria (Universitas Negeri Medan, 2021)
This type of research is R&D Research (Research and Development). This study uses a 4-D development model, which consists of the stages of definition (define), design (design), development (develop), dissemination (disseminate). The instrument used is expert validation, teacher and student responses. The results of the developed media research show: (1) Interactive multimedia based on macromedia flash on theme 8 sub-theme 2 in elementary school is declared very valid with an average score of 90.6% media experts, experts material 92% and linguists 88%, (2) The responses of teachers and students to the interactive multimedia trial based on macromedia flash 8 on theme 8 sub-theme 2 in elementary school obtained a very practical category with an average value of 92.5% and 88% (3 ) The response of teachers and students to the distribution of interactive multimedia based on macromedia flash 8 on theme 8 sub-theme 2 in elementary school obtained a very practical category with average values of 95% and 82.6%Keywords: Development, Macromedia Flash, 4-D Model